Proses Rekrutmen dan Seleksi Pada PT Jamsostek (Persero) Pusat - endang suparni (Widya Cipta - Jurnal Sekretari dan Manajemen, 2017)
The implementation of the recruitment is important in search of new employees that has the quality of very difficult , especially the having particular qualification .Especially on pt jamsostek ( persero ) the center of working in the area of security labor trying to recruit and choose an employee with position in accordance with inventiveness and skill , remember the purpose recruitment and selection on PT Jamsostek (Persero) Centre, is to got the right and able to function optimally.Research methodology used writer is the method descriptive               with a qualitative approach. In the process recruitment and selection on PT Jamsostek (Persero) Centre, be done in online, covering, among other: 1. Publication job application, 2. Received a letter job application, 3.Delivery job application, 4. Building a database, 5. Administrative selection, 6. The transmission of letters call, 7. The implementation of the selection online, 8. The implementation of the selection, 9. The implementation of the selection health and interview user, 10. The implementation of  the training preparation work (dpk),                  11. Removal of candidates an employee (probation 3 months), 12. Removal of permanent workers. The implementation of the recruitment and selection PT Jamsostek (Persero) Centre use the third party. System on the line test recruitment and selection is conducted objectively by the lppm and management human resources PT Jamsostek (Persero) Centre. .